The performance of mortar containing added metakaolin regarding sulfate action - Janneth Torres Agredo; Ruby Mejía de Gutiérrez; Constanza Gutiérrez (Ingeniería e Investigación, 2008)
This paper evaluates the performance of adding Colombian metakaolin (MK) to mortar when these are submitted to sulphate action. Four proportions of MK were used as cement replacement in this study: 10%, 20%, 35% and 50% by weight of cement; cement having 11% tricalcium aluminate was used. Mortar specimens were immersed in 5% sodium sulphate solution for a total period of 280 days after the specified initial moist curing period, The degree of sulphate attack was evaluated by measuring the mortar’s cylindrical expansion, mortar cubes’ compressive strength reduction and visual inspection of mortar specimens. An additional study using X-ray diffraction was conducted to determine the products formed in the cement pastes due to the sulphate attack. The results showed that MK mortar sulphate resistance increased when increasing MK replacement level. An MK proportion greater than 20% is re-commended for obtaining better performance against sulphate attack.